Adding ribavirin to newer DAA regimens does not affect SVR rates in HCV genotype 1 infected persons: results from ERCHIVES. Issue 7 (26th July 2016) - Butt, A. A.; Yan, P.; Marks, K.; Shaikh, O. S.; Sherman, K. E.; ,
Summary: Background: Ribavirin is a key component of several hepatitis C virus (HCV) treatment regimens. However, its utility in combination with newer directly acting anti‐viral agents regimens is unclear. Aim: To determine the SVR rates with paritaprevir/ritonavir/ombitasvir/dasabuvir (PrOD) regimen ± ribavirin and compare this with sofosbuvir/simeprevir and sofosbuvir/ledipasvir regimens. Methods: We used Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES), a well‐established national cohort of HCV‐infected Veterans to identify HCV genotype 1 infected persons initiated on the above regimens. We excluded those with HIV coinfection, positive HBsAg and missing HCV RNA. Results: We identified 1235 persons on PrOD (75.5% ribavirin), 1254 on sofosbuvir/simeprevir (16.9% ribavirin) and 4247 on sofosbuvir/ledipasvir (23.3% ribavirin). Among HCV genotype 1a infected persons, ribavirin was prescribed to 99.2% on PrOD, 18.2% on sofosbuvir/simeprevir and 23.3% on sofosbuvir/ledipasvir. The SVR rates ranged from 92.6% to 100% regardless of the treatment regimen, presence of cirrhosis or HCV subtype, except in PrOD group without ribavirin, HCV genotype 1a without cirrhosis (SVR 80%, N = 5). There were minor, clinically insignificant differences in SVR rates in those treated with or without ribavirin in each of the treatment groups, regardless of presence of cirrhosis at baseline. In multivariable logistic regression analysis, ribavirin use was not associated with achieving SVR in any group. Conclusions: In HCV genotype 1 infected persons, PrOD, sofosbuvir/simeprevir and sofosbuvir/ledipasvir regimens, are associated with high rates of SVR in actual clinical settings, which are comparable to clinical trials results (except PrOD genotype 1a with cirrhosis where the number was too small). The benefit of adding ribavirin to these regimens in the ERCHIVES treated cohort is not established.